A syntax screening test in Tamil - Sudha K Murthy (Journal of All India Institute of Speech and Hearing, 1970)
The present study was designed to investigate the efficacy of a Syntax Screeing Test in Tamil. This test was constructed by the investigator to assess the syntactic development in children and to identify specific areas of syntactic deficits in language disordered children. The Syntax Screening Test was adminstered to fifty-six normal children and three language disordered children.